Challenges Faced by Women Investors in Equity Market Participation - An Empirical Study (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Although women's financial inclusion has been on the rise, their involvement in equity markets remains limited. In order to promote financial inclusion and economic empowerment, it is necessary to gain insight into the influencing factors associated with women's investment choices. This study is designed to investigate the issues of the women's participation in the equity markets, where the impact of investment knowledge, risk perception, and financial literacy, Investor Confidence, Family's Influence, Social Influences, Information Accessibility, Market Complexity and Time Constraints on Equity Market Participation have been analyzed. This research used the strategy quantitative research and data collection techniques is primary data which is obtained from the respondents of this research, namely female investors who are 250 respondents who have been taken. Partial Least Squares Structural Equation Modeling was used to analyze the gathered data. Research results show that Financial Literacy, Information Accessibility, Investor Confidence, Investment Knowledge and Family Influence are important factors which have positive impacts on women's involvement in equity markets. On the other hand, Risk Perception, Market Complexity and Time Constraints were found to have significant negative impacts as these are the main obstacles for investment participation. There was no significant effect of Social Influence on participation decision. The model was strong in explaining the variation of Equity Market Participation with the R square value of 61.55%. The findings indicate that financial education, better access to investment information, greater investor confidence and a streamlined investment process can help to promote women investors' participation. This study helps the growing body of behavioural finance literature by offering a unified model for understanding women's investment decisions and contributes to the expanding corpus of research on developing investor education strategies to encourage women's investment in equity markets as a pathway to financial empowerment and reach gender parity in financial decision-making.